Penentuan Kualitas dan Lingkungan Pengendapan Batubara berdasarkan Nilai Total Abu, Total Air, dan Total Sulphur terhadap Nilai Kalori pada Batubara di Desa Batuah, Kecamatan Loa Janan, Kabupaten Kutai Kartanegara, Provinsi Kalimantan Timur - Muhammad Afrizal Ie; Ahmad Helman Hamdani; Winantris Winantris (Jurnal Geologi dan Sumberdaya Mineral, 2026)
Coal is formed from the accumulation of plant material that undergoes decomposition, compaction, and deposition over millions of years due to physical and chemical influences. This study was conducted in the Kampung Baru Formation, Kutai Basin, to determine quality and depositional environment of coal. Data were obtained from three boreholes (DH-01, DH-02, and DH-03) with having coal thicknesses of 17.8 m, 9.8 m, and 4.8 m, respectively. The analyses performed proximate and ultimate. The results showed that huminite (densinite) was the dominant maceral component with an average of 36.6%, followed by liptinit (cutinite) at 6.8% and inertinite (semifusinite) at 3.03%. The mineral matter content was dominated by pyrite (1.8–6.8%) and clay (0.8–7.6%). The average values of the proximate and ultimate analyses show an ash content of 20.60%, total water of 12.25%, total sulphur of 0.66%, and a calorific value of 4,042.3 cal/g. Based on the United Nations (1998) and ASTM classifications, coal in the study area is categorized as a lignite B to low-medium rank coal. Depositional environment analysis is based on Lamberson diagram classification (1991), which shows that the coal was deposited in a limno-telmatic zone with a lower to upper delta plain facies. Keywords: Coal, Kutai Basin, Kampung Baru Formation, Quality, Depositional Environment, Maceral